Opportunities and challenges of using blockchain technology in government accounting in Brazil - Paula Raymundo Prux (Associação Nacional de Pós-Graduação e Pesquisa em Administração (ANPAD), 2021)
New technologies lead to significant changes in how public and private organizations structure their processes and activities. This study aims to identify the challenges and opportunities of using blockchain technology in government accounting in Brazil. This is a descriptive research using quantitative and qualitative data, collected through a questionnaire applied to a non-probabilistic sample of 94 professionals. The data were submitted to descriptive statistical analysis and content analysis, based on seven categories: technology, government accounting, security, transparency, control, change, and knowledge. For 89.4% of respondents, blockchain can improve government accounting and be applied to financial transactions, auditing, and asset transfers. The technology offers the benefits of trust and control, information security, and control against fraud and corruption. For 98.9% of the sample, the challenges of using blockchain technology in government accounting are the lack of knowledge about the technology and its cost-benefit and implementation, difficulties in replacing or adapting systems, and few blockchain use cases demonstrating the technology’s use and application.